KIAT WANITA KARIER DALAM MENDISIPLINKAN ANAK UNTUK MENGELOLA UANG SAKU DI PERUMAHAN WONOREJO KECAMATAN KEDUNGJAJANG KABUPATEN LUMAJANG - Dian Ika Puspita Sari; Sukidin Sukidin (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
This study was conducted to describe the career woman in disciplining tips to manage your child pocket money a child in the District Housing Wonorejo Kedungjajang Lumajang. Method of determining the location of research using purposive method that area in the District Housing Wonorejo Kedungjajang Lumajang. Technique of determining the research informants using purposive sampling. Subject of research is a career woman in Housing Wonorejo District of Kedungjajang Lumajang as many as 43 people, to key informants namely 5 career women who have children of school (junior high or senior high school) and to the informant as much additional 5 children middle school age (junior or senior). Data collection methods consisted of interviews, observation, and documents. Analysis of the data to be used are data reduction, data presentation (Display Data), and conclusions or verification. The results showed that the issue of women's career in child discipline to manage pocket money includes teaching children to save money in the bank, records all transactions spending money, provide an understanding of the difference between needs and wants, to teach future planning, teaching children to share with others, and reducing the impact of advertising on children's consumer goods. So, with the few efforts were made by the old man with the hope to discipline children in managing pocket money, children can respond to the education savings made by parents. In this case the child becomes interested in saving money as well as better understand the benefits of saving for their future lives.